Dampak Buyback Saham terhadap Abnormal Return pada Bank Badan Usaha Milik Negara di Bursa Efek Indonesia Tahun 2025 - I Gede Yoga Satya Ariarta; Ni Made Suci (Institut Nalanda, 2026)
This study analyzes the impact of share buyback announcements on abnormal returns at State-Owned Enterprises (SOE) banks listed on the Indonesia Stock Exchange (IDX) in 2025. Using an event study approach, this quantitative study observed stock price movements for 11 days, 5 days before and 5 days after the announcement, with a 60-day estimation window using 1-hour intraday data from historical Indonesia Stock Exchange (IDX) data obtained through the TradingView platform and aligned with the official website www.idx.co.id. The sample was selected using a purposive sampling method. Abnormal returns were calculated using a market model and then tested using the Paired Sample t-Test and Wilcoxon Signed Rank Test in SPSS and Excel. The results showed that buyback announcements did not result in significant differences in abnormal returns at Bank Rakyat Indonesia and Bank Mandiri. Conversely, a significant difference was found at Bank Negara Indonesia. Cumulatively, there was a significant difference in average abnormal returns for SOE bank stocks before and after the buyback announcement.